Performance analysis of riceberry rice supply chain in Thailand - W. Wattanutchariya (2018)
© 2017 IEEE. This research aimed to evaluate the performance of the Riceberry rice supply chain in Thailand - from producer to rice mill to end seller - using data collected from site visits and interviews. To evaluate the supply chain, we used the Logistic Performance Index based on Inventory Holding Cost per Sales, Transportation Cost per Sales, Average Inventory Day, Forecast Accuracy Rate, Rate of Return Goods, Warehousing Cost per Sales, Average Order Cycle Time, Average Delivery Cycle Time, and Transportation DIFOT Rate. The key factors that enhanced the performance and sales volume of the supply chain were market expansion, product processing, transportation plan, warehouse management, and customer demand forecasting. These factors can reflect the sales volume of Riceberry rice. A good transportation plan and better warehouse management can reduce the total cost and enhance the performance of the supply chain, while the accuracy of customer demand forecasting can also increase customer satisfaction.